Back Cover: Carbon Neutralization, Volume 1, Issue 1, June 2022. Issue 1 (31st July 2022) - Wang, Zichun; Arstad, Bjørnar; Wang, Leizhi; Ling, Huajuan; Shi, Jeffrey; Stampfl, Catherine; Jiang, Yijiao; Huang, Jun
Abstract : Back cover image: Ca/AlOx catalysts are one of the most popular catalysts in promoting ketonization of carboxylic acids, for bio‐oil upgrading and producing bio‐derived chemicals. However, the commercialization of these catalysts suffers from unclear active sites and significant deactivation in long‐term use. Alkaline‐metal addition can improve their activity and stability. In article number 10.1002/cnl2.4, Huang and co‐workers reported the design of ultra‐stable Ca/AlOx catalysts upon Na addition, the resulting NaAlO2 populated Ca/AlOx catalyst can provide 100% acetone selectivity at the complete conversion of acetic acid at 400 °C beyond 400 h reaction, which paves the way for ration design of high‐performance catalysts for ketonization reactions.